Design of Non-Invasive Glucometer using Microcontroller ATMega-8535 - Hidayanto, Eko; Sutanto, Heri; Arifin, Zaenal (JURNAL SAINS DAN MATEMATIKA, 2015)
Symptoms of Diabetes Mellitus (DM) or diabetes could be indicated by measuring blood sugar levels in the body. One of the health technology to detect blood sugar in non-invasive is to utilize the absorption of laser light and oxymeter sensor capable of generating a voltage change on a variety of fluid medium. This study has been designed using the blood sugar measuring device microcontroller ATMega 8535 as a minimum system in controlling the value of output in the form of data digital. System/equipment to be fabricated in this study is a non-invasive method (without injuring the patient's body when taking a blood sample) to determine the blood sugar content by exploiting the physical properties of absorption of laser sensors on a variety of blood sugar content. To improve the quality of the test data used 8-bit microcontroller that is capable of separating the output data 256 bits (binary). Each of these bit values can be used to replace manual sensor test results that have analogue voltage output of the data. This analogue data will then be converted to analogue to digital converter (ADC) into digital values are displayed in the liquid crystal display (LCD) that is directly readable by the measured/patients in a short period of time less than 5 minutes. The results of the research can be developed into a national program providing portable medical test equipment is cheap and movable. Keywords: DM, Blood Sugar, Sensor of Oxymeter, Red Laser, Microcontroller ATMega 8535